Pengaruh Celebrity Endorsement, Pemasaran Media Sosial, dan Citra Merek terhadap Niat Beli Online pada Marketplace Blibli : Studi Kasus Daerah Istimewa Yogyakarta - Nuroniyah, Navisatun; Rizki Wahyuning Damayanti (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The study aims to determine the effect of celebrity endorsement, social media marketing, and brand image on online purchase intentions at the Blibli marketplace in the Special Region of Yogyakarta. This study uses a quantitative approach with a sample size of 175 respondents who have made at least one purchase at the Blibli marketplace. The sampling technique used is non-probability sampling using the purposive sampling method. The analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS software version 27. The results in this study show (1) Celebrity endorsement has a positive and significant effect on online purchase intentions at the Blibli marketplace. (2) Social media marketing has a positive and significant effect on online purchase intentions at the Blibli marketplace. (3) Brand image has a positive and significant effect on online purchase intentions in the Blibli marketplace. (4) Celebrity endorsement, social media marketing, and brand image simultaneously have a positive and significant effect on online purchase intentions at the Blibli marketplace.